Spreading depolarizations in a case of migraine-related stroke - Santos, Edgar; Sánchez-Porras, Renán; Dohmen, Christian; Hertle, Daniel; Unterberg, Andreas; Sakowitz, Oliver (Cephalalgia, 2012)
BACKGROUND: Cortical spreading depolarization (CSD) has been implicated in the pathophysiology of migraine with aura. Patients that suffer from this type of migraine have shown a higher risk of developing an ischaemic stroke. CASE: A 42-year-old female exhibited reoccurring migraine attacks for the first time 1 month before suffering an ischaemic infarction. Imaging studies revealed an occlusion in the right middle cerebral artery. Other possible disorders were excluded. It was possible to register 20 CSDs, of which 12 coincided with high levels of glutamate and lactate/pyruvate ratio. Loss of lectrocorticographic activity was observed for 89 hours after the 8th depolarization. CONCLUSIONS: Migraine with aura symptoms may be induced by CSDs triggered by hypoperfusion states. Our case supports the idea of the migraine with aura-stroke continuum.